Marx and the ontology of the common - Álvaro, Daniel (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The connecting thread of this work is the idea of the common within the thought of Marx. In the tradition that he inaugurates –as in many of the great political, social and philosophical traditions– the common has a double statute: the ontological and the historical social. In this work we consider both dimensions of analysis from their counterpoints or, more precisely, from their interlacement. On the one hand, we attempt to consider the special relation that Marx establishes between them, while on the other hand and at the same time, we try to emphasize the implications and the radicalism of this other way of thinking, simultaneously, both the “being” and the “social”.